Legal, Accounting and Tax Implications of the Lending Cartel Case 05/KPPU-I/2025 in Indonesia - Grace Grace; Chindy Flawdia Putri; Mutiara Rizqi Nur Rachmi; Josmar Munthe; Puguh Aji Hari Setiawan (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This research examines the case Number 05/KPPU-I/2025, and states that about 97 peer-to-peer (P2P) lending platforms were found guilty of cartel practices by fixing daily interest rates at 0.8%. Komisi Pengawas Persaingan Usaha (KPPU) imposed fines amounting to IDR 755 billion. This decision was upheld by the Supreme Court’s Judicial Review in 2026. Upon basic legal overview, this research also discussed the interdisciplinary chain reaction triggered by this antitrust ruling. The second point of view is from an accounting perspective, discussing margin compression and capital depletion caused by fines that required platforms to aggressively reclassify loan portfolios into Stage 2 and 3 under PSAK 109. This reclassification will make a sharp spike in Allowance for Impairment Losses, and impacting the platform’s profitability and capital adequacy. From A Taxation point of view, this research also dis-cussed the structural friction between PSAK 109 predictive, forward-looking Expected Credit Loss (ECL) provisioning and the Directorate General of Taxes’ retrospective, realization-based approach to bad debts under Minister of Finance Regulation No. 69/PMK.03/2022. The difference between ac-counting and taxation; creates a permanent book-tax gap, thus inflating the Effective Tax Rate (ETR) when platforms are under extreme cash flow duress. Using an empirical juridical qualitative case study design, this research will reveal the systemic bottlenecks in inter-agency data sharing between the KPPU and Otoritas Jasa Keuangan (OJK) under Law No. 4/2023.